Observation of multiramp fractional vortex beams and their total vortex strength in free space. (November 2020) - Wen, Jisen; Gao, Binjie; Zhu, Guiyuan; Cheng, Yibing; Zhu, Shi-Yao; Wang, Li-Gang
Highlights: The propagation properties of multiramp fractional vortex beams propagating in free space is observed. A clear rule of the total vortex strength as a function of topological charge for multiramp fractional vortex beams is found. The total vortex strength is confirmed experimentally via measuring vortex structure by interference method. Abstract: Fractional vortex beams (FVBs) have increasingly attracted attention in recent years due to their complex but interesting topological structures and orbital angular momentum. However, the issue about the total vortex strength of practical FVBs propagating in free space has so far proved inconclusive. Here, we have further experimentally investigated the evolution properties of multiramp fractional vortex beams (MFVBs) including FVBs in free space, and we have systematically revealed the dependence of the total vortex strength on both the non-integer topological charge α and the multiramp number m, which are the parameters of the initial multiramp phase structures of MFVBs. In near-field regions, the vortices contained in MFVBs are unstable, and they change and evolve as the propagation distance increases, therefore it is hard to confirm effectively their vortex strength. However, in far-field regions, the evolution of vortices in fields becomes stable, thus it is considerably easy to determine the value of the vortex strength experimentally via measuring vortex structures by the interference method. Our result shows that the vortex strength for practical FVBs and MFVBs has the different behavior compared with the ideal plane-wave FVBs and MFVBs. These findings give us an understanding of such light fields of both FVBs and MFVBs and may be useful to potential applications related to light signal process and propagation.